Comparison of sawdust and kenaf core fibre as cultivation substrates for grey oyster (Pleurotus sajor-caju) and black jelly (Auricularia auricular-judae) mushrooms. Issue 1 (May 2021) - Ibrahim, R; Shaharudin, N F U
Abstract: Unlike plants, mushrooms are heterotrophic organisms which require external nutrients to grow the hypha network which supplies nutrients for the growth of reproductive stage. In this study, rubber tree sawdust, kenaf core fibre and mixture of sawdust-kenaf (50:50) were used as the cultivation substrates for grey oyster ( Pleurotus sajor-caju ) and black jelly ( Auricularia auricula-judae ) mushrooms. Kenaf ( Hibiscus cannabinus L.) composed of fibre-rich substances which consist of an internal woody core and a superficial fibrous bark. This study was conducted to compare between sawdust and kenaf core fibre as the cultivation substrates in terms of growth performance, yield and postharvest quality of grey oyster and black jelly mushrooms. There was no significant difference (P≥0.05) observed in the mycelium growth rate among the substrates used. However, grey oyster mushroom showed higher growth rate 0.74-0.77 cm/day) compared to black jelly mushroom (0.44-0.55 cm/day). Sawdust substrate showed the highest yield (415.5 g) for both mushroom species followed by mixture of sawdust-kenaf and lastly kenaf. There was also no significant different (P≥0.05) found in the postharvest quality of both mushrooms species among different substrates used. In conclusion, in terms of yield, sawdust was the best mushroom cultivation substrate for both grey oyster and black jelly mushrooms.